Database and Expert Systems Applications 22nd International Conference, DEXA 2011, Toulouse, France, August 29 - September 2, 2011, Proceedings, Part II - Hameurlain, Abdelkader; Liddle, Stephen W.; Schewe, Klaus-Dieter.; Zhou, Xiaofang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 22 International Conference on Database and Expert Systems Applications, DEXA 2011, held in Toulouse, France, August 29 - September 2, 2011. The 52 revised full papers and 40 short papers presented were carefully reviewed and selected from 207 submissions. The papers are organized in topical sections on XML querying and views; data mining; queries and search; semantic web; information retrieval; business applications; user support; indexing; queries, views and data warehouses; ontologies; physical aspects of databases; Design; distribution; miscellaneous topics.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery